Sexual functions in individuals with inflammatory bowel diseases - Marta Kotkowicz-Szczur; Edyta Szymańska; Rafał Kisielewski; Jarosław Kierkuś (Gastroenterology Review)
Problems with intimacy and sexuality are one of the major concerns of patients with inflammatory bowel diseases (IBD). Many symptoms, complications, and consequences of these disorders are likely to impact on body image, intimacy, and sexual function. Moreover, mood disorders, in particular depression, which is a major risk factor for sexual dysfunctions, are reported to be common in chronic illnesses such as IBD. However, despite this obvious relevance, sexual problems are rarely addressed in the clinical management of patients with IBD. The aim of this review was to discuss sexual problem in people with IBD.